Proyecto educativo: maternidad-paternidad como proyecto de vida de los adolescentes (1998)
ABSTRACT: This project analyses the problems to which Colombia adolescence population is forced. The problems they have lived range from the general (concerning their ages) and the specific (concerning the generation) within the context of society in social, economic, and cultural crises as well as communication breaking-off which demands a complex capacity of adaptation. If this adaptation is not achieved by adolescents, they will face conflicts with themselves, the family, the school, and the community; the consequences reflect on social problems as violence and non-desired paternity-maternity. In the latter, non-stable free unions prevail, which leads adolescentes to asume the upbringing of their children. In order to approach these problems, this project tries to promote a behavior of self-esteem, respect, freedom, responsible will, equality, integrity, and self-care by means of health promotion strategies. This behavior will favor their life of achieve an effect on the the decision of having a baby. So that this decision should be a planned process in their life project as a contribution to their welfare and reproductive health. In this way, the incidence of non-desired pregnancy and the social impact will be influenced. This project is supported within a social, institutional, and theoretical-conceptual framework.